ANALISIS PENERBITAN LAPORAN SURVEYOR PADA EKSPOR KONDENSAT MT. NEW ADVANCE DI HUSKY AREA MADURA STRAIT MARINE TERMINAL - Nur Rohmah; Darul Prayogo; Diyan Pratiwi (Politeknik Ilmu Pelayaran Semarang, 2019)
ABSTRACT Husky-CNOOC Company Madura Limited (HCML) is a representative of the Government of the Republic of Indonesia to carry out oil and gas exploration and exploitation activities including condensate in the Madura Strait Block. Condensate will be distributed to domestic and foreign buyers. The factor influencing the smooth export in HCML is the completeness of the Goods Export Notification (PEB) documents in the form of a surveyor (LS) report. If LST does not issue, the company's quota will not be fulfilled as planned. This study aims to determine the flow, constraints, and efforts made in issuing survey reports on MT condensate exports. New Advance in the Husky Area Madura Strait Marine Terminal. The writer uses a qualitative descriptive method by explaining the data in detail based on the facts. For data collection methods, the authors make observations, interviews, documentation, and literature studies. To publish surveyor reports there are several stages that must be carried out along with the completeness of supporting documents such as Export Approval Letter (SPE). In the conduct of MT condensate exports. New Advance found obstacles in the issuance of surveyors because SPE had expired and bad weather at Madura Strait Marine Terminal. Efforts were made to overcome this by meeting with relevant parties such as INSW (Indonesian National Single Window), Ministry of Trade, SKK Migas, and Central Customs and Excise , check SPE documents regularly and establish good communication between parties